Mass timber wall splice connection using glued-in rods: Design methodology, implementation, and shake-table testing in a six-story building - Steven Kontra; Andre R. Barbosa; Arijit Sinha; Steve Pryor; Reid B. Zimmerman; Barbara Simpson; John W. van de Lindt; Shiling Pei; Gustavo A. Araújo R.; Morgan McBain; Ludovica Pieroni; Prashanna Mishra; et al. (Engineering Structures, 2026)

Celebrating the Life of Dr. Andrew “Andy” Bakun - Francisco E. Werner; Jürgen Alheit; Vera Agostini; Steven Bograd; John Field; Anne B. Hollowed; Salvador Lluch‐Cota; Nate Mantua; R. Ian Perry; Ryan R. Rykaczewski; Frank Schwing; Justin Suca (Fisheries Oceanography, 2026)

Conservation genomics of Pecos pupfish ( Cyprinodon pecosensis ) - Elizabeth P. Dolan; Andrew T. Fields; Megan G. Bean; Robyn R. Doege; Joanna L. Hatt; Kevin W. Conway; David S. Portnoy (Journal of Fish Biology, 2026)
The Pecos pupfish, Cyprinodon pecosensis , is an imperilled freshwater fish found in arid regions of Texas and New Mexico (USA). The species faces multiple challenges to persistence including reductions in suitable habitat, water shortages, as well as hybridization and competition with an introduced congener (sheepshead minnow, C. variegatus ). As part of the current management strategy, refuge populations, seeded with non‐introgressed individuals collected from Texas, are maintained at the Fort Worth Zoo and on private property in West Texas. Therefore, assessments of standing genetic variation within and among wild and refuge populations and levels of admixture in the wild are critical for future conservation and management planning. Fin clips were acquired in 10 locations in the wild, five in Texas, five in New Mexico and from two refuge populations in Texas (one maintained by Fort Worth Zoo and another on a private property in West Texas). In Texas, non‐introgressed C. pecosensis were found in the wild at only one location Upper Salt Creek (USC); all other locations were composed of admixed individuals or non‐introgressed C. variegatus . No admixed individuals were found in New Mexico. Significant genetic heterogeneity was detected between all locations of non‐introgressed C. pecosensis , including the refuge populations, and estimates of divergence between Texas locations (USC and refuge populations) and New Mexico locations were relatively large ( F ST : 0.23–0.32). Estimates of contemporary effective population size for USC and the two refuge populations were less than 50, but greater than 500 for all New Mexico populations. In summation, while New Mexico populations look secure, the data suggest that C. pecosensis in Texas is currently imperilled by the threat of hybridization, as well as potential loss of genetic diversity on contemporary time scales. Deep divergence between Texas (including refuge populations) and New Mexico suggests that further study would be needed prior to any management plans that would involve assisted gene flow between the regions.

Vitamin B12 improves skeletal muscle mitochondrial biology in aged mice - Abigail R. Williamson; Angad Yadav; Wenxia Ma; Susan Schmitt; Shelby Rorrer; Lauren E. Odom; Luisa F. Castillo; Chloe T. Purello; Olga V. Malysheva; James Mobley; Martha Field; Anna E. Thalacker-Mercer (GeroScience, 2026)
Age-related skeletal muscle deterioration is a commonly reported disability among older adults, attributed to several factors including mitochondrial dysfunction, a major hallmark of aging. Therapies to attenuate or reverse mitochondrial decline are limited. Despite identified positive relationships between vitamin B12 (B12) and mitochondrial biology, the impact of B12 supplementation on skeletal muscle mitochondria, in advanced age, has not been examined. Thus, the impact of B12 supplementation on skeletal muscle mitochondrial biology was examined in aged female mice, given 12 weeks of B12 supplementation (SUPP) or vehicle control. In the mouse model, mitochondrial DNA and content were measured with PCR and citrate synthase activity, respectively; mitochondrial morphology was examined using transmission electron microscopy; mitochondrial function was examined using extracellular metabolic flux analysis; and proteins and pathway enrichment was identified with proteomics. The results demonstrated that SUPP in aged mice increased muscle mitochondrial content and improved morphology. Further, differentially expressed proteins were enriched in TCA cycle, OXPHOS, and oxidative stress pathways. This is the first study, to our knowledge, examining the impact of B12 supplementation on skeletal muscle mitochondrial biology in aged female mice. Results suggest that B12 supplementation improves mitochondrial biology in aged female mice.

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

Chlorella SLA-04 growth responses to dark period non-circulating, low light conditions in low and high alkalinity - Jessica D. Wood; Isaac R. Miller; Adrienne D. Arnold; Sridhar Viamajala; Robin Gerlach; Matthew W. Fields (Algal Research, 2025)

We Need the Largest Experiments on Earth to Achieve Our Climate Targets - Bronson W. Griscom; Susan C. Cook‐Patton; Erin Sills; Kelsey Jack; Thomas W. Crowther; Sebastien Costedoat; Christopher Field; David Hole; Lisa M. McCullough; Subhrendu K. Pattanayak; Sassan Saatchi; Will R. Turner (Global Change Biology, 2025)

Strong Bottlenecks Constrain Adaptive Coevolution in a Host–Parasite Metapopulation - Pascal Angst; Christoph R. Haag; Frida Ben‐Ami; Peter D. Fields; Dieter Ebert (Molecular Ecology, 2025)
Although parasites are well‐known for adaptively evolving in order to exploit their hosts, they may experience strong genetic drift during transmission bottlenecks when infecting a new host. Host population structure and host population bottlenecks can also lead to genetic drift effects in parasite populations, constraining their adaptive evolution further. Here, we investigate the role of host population structure on the evolution of the microsporidian parasite Hamiltosporidium tvaerminnensis in a dynamic metapopulation of its microcrustacean host Daphnia magna . In following whole‐genome allele frequencies of 59 host and parasite subpopulations for up to 10 years, we found that both antagonists showed patterns of co‐dispersal and isolation‐by‐distance, but allele frequencies were much more dynamic in the host, where we found signatures of recurrent genetic bottlenecks. In the parasite, we observed high levels of shared heterozygosity among subpopulations but also subpopulation‐specific runs of homozygosity (ROHs). We hypothesise that deleterious ROHs, which originate from loss of heterozygosity events during asexual recombination, are fixed in subpopulations following host‐mediated parasite population bottlenecks when host and parasite co‐disperse into a habitat patch where the parasite is not yet present. Thus, host population structure and metapopulation dynamics leave a clearly traceable genomic signature in the coevolving parasite. Contrary to the prevailing assumption that parasites evolve at higher rates than their hosts, our study not only suggests that parasites can evolve more slowly than their host, but also that host dynamics can accelerate drift processes in the parasite.

The essential role of large research vessels in marine ecosystem observations and ocean sustainability - Erin V. Satterthwaite; John C. Field; Andrea J. Fassbender; Gerardo Aceves‐Medina; Steven J. Bograd; Elliott L. Hazen; Nastassia V. Patin; Zachary Gold; Katherine A. Barbeau; Danie Kinkade; Adam Shepherd; Rasmus Swalethorp; et al. (Limnology and Oceanography, 2025)
Our understanding of marine ecosystems and ability to manage them sustainably has come from multidisciplinary observations made repeatedly over long periods of time. These long‐term ecosystem observations depend on the capabilities of large research vessels, which play an essential role in the collection of global ocean observations. Research vessels serve as large, stable platforms for collecting high volume samples from the surface to the seafloor that provide uniquely valuable in situ marine ecosystem information. Additionally, they serve as mobile laboratories enabling the collection, preservation, processing, and analysis of unique samples and data, such as chemical, biogeochemical, and biological parameters. Given their capacity for, and repeated use in, collecting comprehensive marine ecosystem observations—across geology, physics, chemistry, and biology—large research vessels provide insight into long‐term regional ecosystem dynamics. They also act as platforms‐of‐opportunity for testing, refining, and comparing technologies, enabling innovation and the evolution of the observing system. High‐quality observations from large research vessels serve as the backbone for many other components of the global ocean observing system through their use in calibrating autonomous sensors and predictive modeling. Moreover, large research vessels function as mobile, experiential training and exploration platforms that facilitate discovery, education, and collaboration. An effective, modular marine ecosystem observing system will depend on large research vessels to sustain and augment existing observing programs and to deploy, service, and validate the growing array of autonomous platforms that contribute to it. Achieving this vision will likely require maintaining and upgrading ship‐based infrastructure and personnel, integrating emerging technologies, leveraging the unique capabilities of large research vessels in conjunction with other platforms, strengthening collaborative partnerships, and building social capital for marine ecosystem observations through training, knowledge sharing, and effective governance.

Comprehensive Characterisation of the RFC1 Repeat in an Australian Cohort - Kayli C. Davies; Haloom Rafehi; Liam G. Fearnley; Penny Snell; Greta Gillies; Tess A. Field; Gábor M. Halmágyi; Kishore R. Kumar; Kate Pope; Renee Smyth; Susan E. Tomlinson; Stephen Tisch; et al. (The Cerebellum, 2025)

Conceptualizing core aspects of circular economy in soil: A critical review and analysis - Chukwudi Nwaogu; Budiman Minasny; Damien J. Field; Mauricio R. Cherubin (Critical Reviews in Environmental Science and Technology, 2025)

Taphonomic damage obfuscates interpretation of the retroarticular region of the Asteriornis mandible - Abi Crane; Juan Benito; Albert Chen; Grace Musser; Christopher R. Torres; Julia A. Clarke; Stephan Lautenschlager; Daniel T. Ksepka; Daniel J. Field (Geobios, 2025)

Corrigendum to “Effect of temperature, nitrate concentration, pH and bicarbonate addition on biomass and lipid accumulation in the sporulating green alga PW95.” [Algal. Res. 53: 102148] - L. Corredor; E.P. Barnhart; A.E. Parker; R. Gerlach; M.W. Fields (Algal Research, 2025)

Towards a comprehensive geodiversity - biodiversity nexus in terrestrial ecosystems - C. Beierkuhnlein; B. Pugh; S. Justice; F. Schrodt; G. El Serafy; A. Karnieli; I. Manakos; L. Nietsch; J. Peñas de Giles; A. Peterek; D. Poursanidis; Z. Zwoliński; et al. (Earth-Science Reviews, 2025)

Correction: The history, science and preliminary results from the reintroduction of the chequered skipper, Carterocephalus palaemon into Rockingham forest, England - N. A. D. Bourn; S. O’Riordan; D. Maes; P. Goffart; T. Shadbolt; L. Hordley; A. W. Sainsbury; C. Bulman; D. Hoare; R. Field; J. Curson; J. P. Wildman; et al. (Journal of Insect Conservation, 2025)

Microbial remediation of insensitive munitions compounds and their transformation products: from biodegradation mechanisms to engineered strategies - O. Menezes; R. Sierra-Alvarez; J. A. Field (Reviews in Environmental Science and Bio/Technology, 2025)

Assessment of genomic diversity within and between two cryptic shiners, the West Texas shiner ( Notropis megalops ) and the Texas shiner ( Notropis amabilis ) - Kayla R. Dye; Andrew T. Fields; Megan G. Bean; Sarah M. Robertson; Christopher M. Hollenbeck; Kevin W. Conway; David S. Portnoy (Journal of Fish Biology, 2025)
The presence of cryptic species can hinder effective conservation planning and implementation, as has been the case for speciose groups of freshwater fishes that are difficult to differentiate due to conserved morphologies. The West Texas shiner Notropis megalops and the Texas shiner Notropis amabilis are a cryptic pair of leuciscids (minnows) that co‐occur in spring‐fed tributaries of the Rio Grande in Texas and Mexico. Both N. megalops and N. amabilis are listed as Species of Greatest Conservation Need by the Texas Parks and Wildlife Department. Notropis amabilis is widespread and listed as apparently secure by Texas Parks and Wildlife Department whereas N. megalops has a very limited distribution and has not been ranked by Texas Parks and Wildlife Department because of data deficiency. Morphological differences between these species have been described; however, proper identification in situ remains problematic. Furthermore, given their range of overlap there is potential for hybridization, and limited genetic data have been collected comparing the species. Therefore, reduced representation genomic and mitochondrial sequencing data were used to reassess the distinctness of the species, screen for hybridization, and characterize their relative frequencies throughout their range of overlap. Genomic analyses recovered two distinct genetic groups corresponding to the species ( F' CT = 0.89) with no evidence of admixture or introgression. The species were found to co‐occur at three sampling locations, two in the Devils River and one in the Pecos, but not in equal frequencies. Overall, these results provide data and tools for further research on N. megalops needed for accurate conservation policies and management practices.

Phycosome dynamics during successive outdoor microalgae cultivation from late summer to fall - I.R. Miller; H. Bui; B. Maddi; S. Viamajala; R. Gerlach; M.W. Fields (Aquaculture, 2025)

Effects of burning on vegetation, soil physicochemistry and prokaryotic microbial communities in surface and subsurface peat - Shaun M. Allingham; Samantha J. Drake; Andrew Ramsey; Chris D. Field; Felix C. Nwaishi; David R. Elliott (Science of The Total Environment, 2024)

Leveraging ecological indicators to improve short term forecasts of fish recruitment - Eric J. Ward; Mary E. Hunsicker; Kristin N. Marshall; Kiva L. Oken; Brice X. Semmens; John C. Field; Melissa A. Haltuch; Kelli F. Johnson; Ian G. Taylor; Andrew R. Thompson; Nick Tolimieri (Fish and Fisheries, 2024)
Forecasting the recruitment of fish populations with skill has been a challenge in fisheries for over a century. Previous large‐scale meta‐analyses have suggested linkages between environmental or ecosystem drivers and recruitment; however, applying this information in a management setting remains underutilized. Here, we use a well‐studied database of groundfish assessments from the West Coast of the USA to ask whether environmental variables or ecosystem indicators derived from long‐term monitoring datasets offer an improvement in our ability to skilfully forecast fish recruitment. A secondary question is which types of modelling approaches (ranging from linear models to non‐parametric methods) yield the best forecast skill. Third, we examine whether simultaneous forecasting of multiple species offers an advantage over generating species‐specific forecasts. We find that for approximately one third of the 29 assessed stocks, ecosystem indicators from juvenile surveys yields the highest out of sample predictive skill compared to other covariates (including environmental variables from Regional Ocean Modeling System output) or null models. Across modelling approaches, our results suggest that simpler linear modelling approaches do as well or better than more complicated approaches (reducing out of sample Root Mean Square Error by ~40% compared to null models), and that there appears to be little benefit to performing multispecies forecasts instead of single‐species forecasts. Our results provide a general framework for generating recruitment forecasts in other species and ecosystems, as well as a benchmark for future analyses to evaluate skill. The most promising applications are likely for species that are short lived, have relatively high recruitment variability, and moderate amounts of age or length data. Forecasts using our approach may be useful in identifying covariates or mechanisms to include in operational assessments but also provide qualitative advice to managers implementing ecosystem based fisheries management.

The history, science and preliminary results from the reintroduction of the Chequered Skipper, Carterocephalus palaemon into Rockingham Forest, England - N. A. D. Bourn; S. O’Riordan; D. Maes; P. Goffart; T. Shadbolt; L. Hordley; A. W. Sainsbury; C. Bulman; D. Hoare; R. Field; J. Curson; J. P. Wildman; et al. (Journal of Insect Conservation, 2024)
Habitat loss and fragmentation have caused declines in the abundance and distribution of butterflies, particularly habitat specialists. The Chequered Skipper, Carterocephalus palaemon , has been extinct in England since 1976 after declining from the 1940s predominantly due to changes in woodland management including afforestation and the decline in traditional coppice management. To enable C. palaemon to flourish again, this species was reintroduced from Belgium to England in 2018 with the aim of establishing a resident breeding population. Here, we report on the recent reintroduction, outlining the reintroduction method used, the establishment status of the species in England, the clinical health of reintroduced individuals, and post-release monitoring results. Furthermore, we assess the habitat suitability of sites around the original release site to determine which were similar to the current re-location site and could be used for future reintroductions, and to aid the targeting of further management to increase habitat suitability. Since 2018, 128 Chequered Skipper butterflies have been reintroduced from Belgium to Rockingham Forest in England. Health examinations demonstrated that individuals were healthy, and this in part resulted in the population establishing at the first release site and the area of occupancy increasing each year to 2022. However, the reintroduced population has yet to naturally colonise other areas within Rockingham Forest and therefore is not yet a functioning metapopulation. Despite the project still being in its infancy, we are able to report on a successful five years. Implications for insect conservation: Rigorous scientific research has provided the evidence to support reintroductions, and will continue to be used to ensure the ecology and population dynamics of this species is sufficiently understood so that Chequered Skipper populations can thrive again in England.

Changes in nitrogen functional genes and microbial populations in soil profiles of a peatland under different burning regimes - Shaun M. Allingham; Samantha J. Drake; Andrew Ramsey; Chris D. Field; Felix C. Nwaishi; David R. Elliott (Applied Soil Ecology, 2024)

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Assessment of oceanographic conditions during the North Atlantic EXport processes in the ocean from RemoTe sensing (EXPORTS) field campaign - Leah Johnson; David A. Siegel; Andrew F. Thompson; Erik Fields; Zachary K. Erickson; Ivona Cetinic; Craig M. Lee; Eric A. D'Asaro; Norman B. Nelson; Melissa M. Omand; Michaela Sten; Shawnee Traylor; et al. (Progress in Oceanography, 2024)

Abiotic reductive transformation of 3-nitro-1,2,4-triazol-5-one by zero-valent iron - Y. Yu; R. A. Root; R. Castrejon Miranda; R. Sierra-Alvarez; J. Chorover; J. A. Field (International Journal of Environmental Science and Technology, 2024)

Cognition mediates response to anthropogenic noise in wild Western Australian magpies ( Gmynorhina tibicen dorsalis ) - Grace Blackburn; Benjamin J. Ashton; Alex Thornton; Sarah Woodiss‐Field; Amanda R. Ridley (Global Change Biology, 2023)
Anthropogenic noise is a pollutant of growing concern, with wide‐ranging effects on taxa across ecosystems. Until recently, studies investigating the effects of anthropogenic noise on animals focused primarily on population‐level consequences, rather than individual‐level impacts. Individual variation in response to anthropogenic noise may result from extrinsic or intrinsic factors. One such intrinsic factor, cognitive performance, varies between individuals and is hypothesised to aid behavioural response to novel stressors. Here, we combine cognitive testing, behavioural focals and playback experiments to investigate how anthropogenic noise affects the behaviour and anti‐predator response of Western Australian magpies ( Gymnorhina tibicen dorsalis ), and to determine whether this response is linked to cognitive performance. We found a significant population‐level effect of anthropogenic noise on the foraging effort, foraging efficiency, vigilance, vocalisation rate and anti‐predator response of magpies, with birds decreasing their foraging, vocalisation behaviours and anti‐predator response, and increasing vigilance when loud anthropogenic noise was present. We also found that individuals varied in their response to playbacks depending on their cognitive performance, with individuals that performed better in an associative learning task maintaining their anti‐predator response when an alarm call was played in anthropogenic noise. Our results add to the growing body of literature documenting the adverse effects of anthropogenic noise on wildlife and provide the first evidence for an association between individual cognitive performance and behavioural responses to anthropogenic noise.

Philopatry influences the genetic population structure of the blacktip shark ( Carcharhinus limbatus ) at multiple spatial scales - Dominic G. Swift; Shannon J. O'Leary; R. Dean Grubbs; Bryan S. Frazier; Andrew T. Fields; Jayne M. Gardiner; J. Marcus Drymon; Dana M. Bethea; Tonya R. Wiley; David S. Portnoy (Molecular Ecology, 2023)
Understanding how interactions among microevolutionary forces generate genetic population structure of exploited species is vital to the implementation of management policies that facilitate persistence. Philopatry displayed by many coastal shark species can impact gene flow and facilitate selection, and has direct implications for the spatial scales of management. Here, genetic structure of the blacktip shark ( Carcharhinus limbatus ) was examined using a mixed‐marker approach employing mitochondrial control region sequences and 4339 SNP‐containing loci generated using ddRAD‐Seq. Genetic variation was assessed among young‐of‐the‐year sampled in 11 sites in waters of the United States in the western North Atlantic Ocean, including the Gulf of Mexico. Spatial and environmental analyses detected 68 nuclear loci putatively under selection, enabling separate assessments of neutral and adaptive genetic structure. Both mitochondrial and neutral SNP data indicated three genetically distinct units—the Atlantic, eastern Gulf, and western Gulf—that align with regional stocks and suggest regional philopatry by males and females. Heterogeneity at loci putatively under selection, associated with temperature and salinity, was observed among sites within Gulf units, suggesting local adaptation. Furthermore, five pairs of siblings were identified in the same site across timescales corresponding with female reproductive cycles. This indicates that females re‐used a site for parturition, which has the potential to facilitate the sorting of adaptive variation among neighbouring sites. The results demonstrate differential impacts of microevolutionary forces at varying spatial scales and highlight the importance of conserving essential habitats to maintain sources of adaptive variation that may buffer species against environmental change.

Long‐term elevated precipitation induces grassland soil carbon loss via microbe‐plant–soil interplay - Mengmeng Wang; Xin Sun; Baichuan Cao; Nona R. Chiariello; Kathryn M. Docherty; Christopher B. Field; Qun Gao; Jessica L. M. Gutknecht; Xue Guo; Genhe He; Bruce A. Hungate; Jiesi Lei; et al. (Global Change Biology, 2023)
Global climate models predict that the frequency and intensity of precipitation events will increase in many regions across the world. However, the biosphere‐climate feedback to elevated precipitation (eP) remains elusive. Here, we report a study on one of the longest field experiments assessing the effects of eP, alone or in combination with other climate change drivers such as elevated CO 2 (eCO 2 ), warming and nitrogen deposition. Soil total carbon (C) decreased after a decade of eP treatment, while plant root production decreased after 2 years. To explain this asynchrony, we found that the relative abundances of fungal genes associated with chitin and protein degradation increased and were positively correlated with bacteriophage genes, suggesting a potential viral shunt in C degradation. In addition, eP increased the relative abundances of microbial stress tolerance genes, which are essential for coping with environmental stressors. Microbial responses to eP were phylogenetically conserved. The effects of eP on soil total C, root production, and microbes were interactively affected by eCO 2 . Collectively, we demonstrate that long‐term eP induces soil C loss, owing to changes in microbial community composition, functional traits, root production, and soil moisture. Our study unveils an important, previously unknown biosphere‐climate feedback in Mediterranean‐type water‐limited ecosystems, namely how eP induces soil C loss via microbe‐plant–soil interplay.

Mortality in an off-shore predator critical habitat during the Northeast Pacific marine heatwave - Casandra Gálvez; Stephen Raverty; Felipe Galván-Magaña; Cara L. Field; Fernando R. Elorriaga-Verplancken (Frontiers in Marine Science, 2023)
Defining baseline mortality and trends in wildlife populations is imperative to understand natural and anthropogenic threats to overall population health and improve conservation measures for species, particularly in geographically confined habitats. The Guadalupe fur seal Arctocephalus townsendi (GFS) is a threatened pinniped that ranges throughout the west coast of Mexico with sporadic dispersion to higher latitudes. Their breeding habitat is restricted to Guadalupe Island, Mexico, which is vulnerable to periodic and cyclic warming of the Northeast Pacific Ocean. The impacts of environmental change on GFS health and reproductive success at Guadalupe Island are poorly defined and the aim of this study was to establish baseline pup (GFS n ) mortality rates and primary causes of death during the 2013-2016 breeding seasons at Guadalupe Island. Interannual mortality rates and causes of death were compared by year, breeding seasons and by geographic location. The highest mortality rate in GFS n was in 2015 (14.7%), followed by 2014 (8.2%), 2016 (6.7%) and 2013 (5.6%). The presumptive causes of mortality of GFS n were consistent with other published long term otariids health surveys and included: emaciation (49%), trauma (24%), infectious disease (8%), drowning (4%) stillbirth/perinatal mortality (4%) and undetermined (11%). However, in 2015 and coinciding with northeast Pacific marine heatwave in 2014-2016, emaciation accounted for 54% of GFS n mortality in contrast to 9% in 2013. For GFS n , terrestrial habitat may influence mortality rates and causes of mortality but like other marine predators, marine habitat features, such as an increase in sea surface temperature are associated with changes in maternal care, nutritional status and pups survival. Monitoring mortality rate and causes in GFS n at Guadalupe Island is crucial to establish baseline health trends, document potential impacts on species demographics and recruitment during marine heatwaves and potential consequences in population recovery.

Evaluating the sustainability of the 2017 US biofuel industry with an integrated techno-economic analysis and life cycle assessment - Jack P. Smith; Braden J. Limb; Colin M. Beal; Kelly R. Banta; John L. Field; Steven J. Simske; Jason C. Quinn (Journal of Cleaner Production, 2023)

Correction to: Analysing the distribution of strictly protected areas toward the EU2030 target - Roberto Cazzolla Gatti; Piero Zannini; Gianluca Piovesan; Nicola Alessi; Alberto Basset; Carl Beierkuhnlein; Michele Di Musciano; Richard Field; John M. Halley; Samuel Hoffmann; Jacopo Iaria; Athanasios Kallimanis; et al. (Biodiversity and Conservation, 2023)

Analysing the distribution of strictly protected areas toward the EU2030 target - Roberto Cazzolla Gatti; Piero Zannini; Gianluca Piovesan; Nicola Alessi; Alberto Basset; Carl Beierkuhnlein; Michele Di Musciano; Richard Field; John M. Halley; Samuel Hoffmann; Jacopo Iaria; Athanasios Kallimanis; et al. (Biodiversity and Conservation, 2023)
Protecting global biodiversity is one of the most urgent tasks for the coming decades. Area-based conservation is a pillar for preserving ecosystems and species. Strictly protected areas specifically preserve biodiversity and ecosystem processes. The “EU Biodiversity Strategy for 2030” targets strict protection for 10% of land area. Here we performed the first analysis of strictly protected areas (as IUCN type Ia, Ib, and II) across Europe, by investigating their area coverage at the level of biogeographical regions, countries and elevation gradients. We show that, with few exceptions, the amount of strictly protected area is very limited and the spatial distribution of such protected areas is biased towards higher elevation sites, as in the case of other protected areas. Then, we suggest that potential areas should be identified to expand strictly protected areas with low economic and social costs including, for instance, areas with high biodiversity value, low population, and low productive land use. Finally, we propose that a coordinated effort and a strategic plan to achieve continental-scale conservation are fundamental, and at least half of this land under strict conservation (i.e. 5%) should be under the protection categories Ia and Ib.

Spatial and temporal variability of per- and polyfluoroalkyl substances (PFAS) in environmental media of a small pond: Toward an improved understanding of PFAS bioaccumulation in fish - Abbi S. Brown; Xiaoyan Yun; Erica R. McKenzie; Christopher G. Heron; Jennifer A. Field; Christopher J. Salice (Science of The Total Environment, 2023)

Age, Growth and Maturity of the Bonnethead Sphyrna tiburo in the U.S. Gulf of Mexico - Bryan S. Frazier; Elizabeth A. Vinyard; Andrew T. Fields; William B. Driggers; R. Dean Grubbs; Douglas H. Adams; J. Marcus Drymon; Jayne M. Gardiner; Jill M. Hendon; Eric Hoffmayer; Robert E. Hueter; R. J. David Wells; et al. (Environmental Biology of Fishes, 2023)

Automated detection, delineation and quantification of whole-body bone metastasis using FDG-PET/CT images - R. Nigam; M. Field; G. Harris; M. Barton; M. Carolan; P. Metcalfe; L. Holloway (Physical and Engineering Sciences in Medicine, 2023)
Non-small cell lung cancer (NSCLC) patients with the metastatic spread of disease to the bone have high morbidity and mortality. Stereotactic ablative body radiotherapy increases the progression free survival and overall survival of these patients with oligometastases. FDG-PET/CT, a functional imaging technique combining positron emission tomography (PET) with 18 F-fluorodeoxyglucose (FDG) and computer tomography (CT) provides improved staging and identification of treatment response. It is also associated with reduction in size of the radiotherapy tumour volume delineation compared with CT based contouring in radiotherapy, thus allowing for dose escalation to the target volume with lower doses to the surrounding organs at risk. FDG-PET/CT is increasingly being used for the clinical management of NSCLC patients undergoing radiotherapy and has shown high sensitivity and specificity for the detection of bone metastases in these patients. Here, we present a software tool for detection, delineation and quantification of bone metastases using FDG-PET/CT images. The tool extracts standardised uptake values (SUV) from FDG-PET images for auto-segmentation of bone lesions and calculates volume of each lesion and associated mean and maximum SUV. The tool also allows automatic statistical validation of the auto-segmented bone lesions against the manual contours of a radiation oncologist. A retrospective review of FDG-PET/CT scans of more than 30 candidate NSCLC patients was performed and nine patients with one or more metastatic bone lesions were selected for the present study. The SUV threshold prediction model was designed by splitting the cohort of patients into a subset of ‘development’ and ‘validation’ cohorts. The development cohort yielded an optimum SUV threshold of 3.0 for automatic detection of bone metastases using FDG-PET/CT images. The validity of the derived optimum SUV threshold on the validation cohort demonstrated that auto-segmented and manually contoured bone lesions showed strong concordance for volume of bone lesion ( r = 0.993) and number of detected lesions ( r = 0.996). The tool has various applications in radiotherapy, including but not limited to studies determining optimum SUV threshold for accurate and standardised delineation of bone lesions and in scientific studies utilising large patient populations for instance for investigation of the number of metastatic lesions that can be treated safety with an ablative dose of radiotherapy without exceeding the normal tissue toxicity.

Radiation Oncology Virtual Education Rotation (ROVER) 2.0 for Residents: Implementation and Outcomes - Navjot K. Sandhu; Elham Rahimy; Ryan Hutten; Utkarsh Shukla; Anne Rajkumar-Calkins; Jacob A. Miller; Rie Von Eyben; Christopher R. Deig; Jean-Pierre Obeid; Rachel B. Jimenez; Emma C. Fields; Erqi L. Pollom; et al. (Journal of Cancer Education, 2023)

Nesting biology and social organisation of a silk wasp (Microstigmus rosae) from the North–West Ecuadorian Choco - R. L. Bonifacii; J. Field (Insectes Sociaux, 2023)
Microstigmus Ducke (Hymenoptera, Apoidea, Crabronidae, Pemphredoninae) is an intriguing genus of wasp, particularly interesting for the study of social evolution as it contains the only species of apoid wasps known to exhibit eusocial behaviours. Thus far, data concerning the genetics and biology of sociality in Microstigmus are restricted to just two species . Through behavioural observations and genetic analyses, we here present a detailed report on the nesting biology and social organisation of a third species, Microstigmus rosae. Our results indicate that M. rosae nests are founded by a single female and social groups appear when emerging female offspring remain on the natal nests as helpers. Adult females mass provision their offspring and developmental data are consistent with sequential brood production, an average egg laying interval of 10 days and a brood developmental period of more than 35 days. Social group formation is atypical, with 20% of nests containing up to a maximum of four adult females and two males. Adult group size is positively correlated with the number of brood in a nest, but negatively correlated with per capita brood. The sex investment ratio was female biased. Our findings support several theories concerning the behavioural characteristics thought to be important for transitions towards sociality, namely: high genetic relatedness generated by monogamous matrifilial associations, hygienic behaviour and the potential for direct reproduction. In contrast, one hypothesised trait, progressive provisioning, is notably absent, highlighting the need for investigations into the significance of post-provisioning parental care for offspring survival in this genus.

A positive temperature‐dependent effect of elevated CO 2 on growth and lipid accumulation in the planktonic copepod, Calanus finmarchicus - David M. Fields; Jeffrey A. Runge; Cameron R. S. Thompson; Caroline M. F. Durif; Steven D. Shema; Reidun M. Bjelland; Maura Niemisto; Michael T. Arts; Anne Berit Skiftesvik; Howard I. Browman (Limnology and Oceanography, 2023)
Calanus finmarchicus were reared from eggs to adults at 12°C and 16°C with non‐limiting food in combination with ambient (600 μ atm) and high (1100 μ atm) p CO 2 . These conditions are likely to be encountered by the species at the southern margins of its biogeographical range by the end of the century. Dry weight (DW), carbon (C) and nitrogen (N) mass, oil‐sac volume (OSV), fatty acid composition (FA), and oxygen consumption rates (OCR) were measured on newly molted stage CV copepodites and recently molted adult females. By focusing our measurements on these precise events in the life cycle, we were able to obtain a more accurate comparison of growth and respiration across treatments. Copepods raised at 12°C had a significantly greater DW, OSV, and C and N mass than those raised at 16°C High p CO 2 , independent of temperature, was associated with a further increase in the DW and C content of the copepods. Interactive effects of temperature and p CO 2 resulted in a larger OSV at low temperature and high p CO 2 . Mass‐specific respiration rates were significantly lower at lower temperatures and elevated p CO 2 suggesting that the increase in mass (DW, C, and OSV) resulted from reduced metabolic cost. The composition of fatty acids in the copepods varied mainly with temperature. Two fatty acids varied with p CO 2 : 16:0 tended to decrease with higher p CO 2 and 18:3n−3 tended to increase with higher p CO 2 . These observations suggest that elevated p CO 2 /lower pH in future oceans may have a beneficial effect on C. finmarchicus .

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

Group differences in binge eating, impulsivity, and intuitive and mindful eating among intermittent fasters and non-fasters - Jordan Schueler; Samantha R. Philip; Darya Vitus; Solangia Engler; Sherecce A. Fields (Appetite, 2023)

Enhancing the review process in global environmental assessments: The case of the IPCC - Jean P. Palutikof; Sarah L. Boulter; Christopher B. Field; Katharine J. Mach; Martin R. Manning; Michael D. Mastrandrea; Leo Meyer; Jan C. Minx; Joy J. Pereira; Gian-Kasper Plattner; Suzana Kahn Ribeiro; Youba Sokona; et al. (Environmental Science & Policy, 2023)

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Radiation Oncology Education Collaborative Study Group Annual Spring Symposium: Initial Impact and Feedback - David M. Rosenberg; Steve E. Braunstein; Emma C. Fields; Erin F. Gillespie; Jillian R. Gunther; Rachel B. Jimenez; Raphael L. Yechieli; Daniel W. Golden (Journal of Cancer Education, 2022)

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Copepod interaction with small‐scale, dissipative eddies in turbulence: Comparison among three marine species - Dorsa Elmi; Donald R. Webster; David M. Fields (Limnology and Oceanography, 2022)
A physical model of a Burgers vortex was created in the laboratory with characteristics corresponding to dissipative‐scale eddies that copepods are likely to encounter in turbulent flows. The swimming behavior of three marine copepod species is assessed as a function of vortex strength in and around the flow structure with the vortex axis aligned vertically or horizontally in the water. The studied species are Acartia tonsa , an estuarine copepod with a hop‐sink swimming style; Temora longicornis , a coastal copepod with a cruise swimming style; and Calanus finmarchicus , an open‐ocean copepod with a cruise‐sink swimming style. The results show that copepods change their swimming behavior with the intensity of the Burgers vortex and reveal species‐specific responses in nearly all kinematic parameters. A. tonsa and C. finmarchicus exhibited the strongest behavioral response to increasing vortex strength and T. longicornis exhibited the weakest response. A. tonsa and T. longicornis showed no response to changes in vortex orientation, whereas the behavior of C. finmarchicus revealed some vortex orientation dependence. One common behavior among the species is that the swimming trajectory shape becomes increasingly curved and spiral around the vortex core with increasing vortex strength, which provides a means of local aggregation and increased encounter rate with food and mates. The results are interpreted in relation to differences in swimming style and setal morphology among the species.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Correction to: Tree-ring cellulose δ18O records similar large-scale climate influences as precipitation δ18O in the Northwest Territories of Canada - Robert D. Field; Laia Andreu-Hayles; R. D. D’arrigo; R. Oelkers; B. H. Luckman; D. Morimoto; E. Boucher; F. Gennaretti; I. Hermoso; A. Lavergne; M. Levesque (Climate Dynamics, 2022)

Higher buccal mitochondrial DNA and mitochondrial common deletion number are associated with markers of neurodegeneration and inflammation in cerebrospinal fluid - Dipesh Solanky; Jerel A. Fields; Jennifer E. Iudicello; Ronald J. Ellis; Donald Franklin; David B. Clifford; Benjamin B. Gelman; Christina M. Marra; Susan Morgello; Leah H. Rubin; Igor Grant; Robert K. Heaton; et al. (Journal of NeuroVirology, 2022)

Mercury exposure of tidal marsh songbirds in the northeastern United States and its association with nest survival - Katharine J. Ruskin; Garth Herring; Collin A. Eagles-Smith; Alyssa B. Eiklor; Chris S. Elphick; Matthew A. Etterson; Christopher R. Field; Rebecca A. Longenecker; Adrienne I. Kovach; W. Gregory Shriver; Jennifer Walsh; Brian J. Olsen (Ecotoxicology, 2022)

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Tree-ring cellulose δ18O records similar large-scale climate influences as precipitation δ18O in the Northwest Territories of Canada - Robert D. Field; Laia Andreu-Hayles; R. D. D’arrigo; R. Oelkers; B. H. Luckman; D. Morimoto; E. Boucher; F. Gennaretti; I. Hermoso; A. Lavergne; M. Levesque (Climate Dynamics, 2022)

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Using fisher‐contributed secondary fins to fill critical shark‐fisheries data gaps - Jessica R. Quinlan; Shannon J. O'Leary; Andrew T. Fields; Martin Benavides; Emily Stumpf; Ramon Carcamo; Joel Cruz; Derrick Lewis; Beverly Wade; George Amato; Sergios‐Orestis Kolokotronis; Gina M. Clementi; et al. (Conservation Biology, 2021)
Developing‐world shark fisheries are typically not assessed or actively managed for sustainability; one fundamental obstacle is the lack of species and size‐composition catch data. We tested and implemented a new and potentially widely applicable approach for collecting these data: mandatory submission of low‐value secondary fins (anal fins) from landed sharks by fishers and use of the fins to reconstruct catch species and size. Visual and low‐cost genetic identification were used to determine species composition, and linear regression was applied to total length and anal fin base length for catch‐size reconstruction. We tested the feasibility of this approach in Belize, first in a local proof‐of‐concept study and then scaling it up to the national level for the 2017–2018 shark‐fishing season (1,786 fins analyzed). Sixteen species occurred in this fishery. The most common were the Caribbean reef ( Carcharhinus perezi ), blacktip ( C. limbatus ), sharpnose (Atlantic [ Rhizoprionodon terraenovae ] and Caribbean [ R. porosus ] considered as a group), and bonnethead ( Sphyrna cf. tiburo ). Sharpnose and bonnethead sharks were landed primarily above size at maturity, whereas Caribbean reef and blacktip sharks were primarily landed below size at maturity. Our approach proved effective in obtaining critical data for managing the shark fishery, and we suggest the tools developed as part of this program could be exported to other nations in this region and applied almost immediately if there were means to communicate with fishers and incentivize them to provide anal fins. Outside the tropical Western Atlantic, we recommend further investigation of the feasibility of sampling of secondary fins, including considerations of time, effort, and cost of species identification from these fins, what secondary fin type to use, and the means with which to communicate with fishers and incentivize participation. This program could be a model for collecting urgently needed data for developing‐world shark fisheries globally. Article impact statement : Shark fins collected from fishers yield data critical to shark fisheries management in developing nations.

Spatial population genomics of a recent mosquito invasion - Thomas L. Schmidt; Tom Swan; Jessica Chung; Stephan Karl; Samuel Demok; Qiong Yang; Matt A Field; Mutizwa Odwell Muzari; Gerhard Ehlers; Mathew Brugh; Rodney Bellwood; Peter Horne; et al. (Molecular Ecology, 2021)
Population genomic approaches can characterize dispersal across a single generation through to many generations in the past, bridging the gap between individual movement and intergenerational gene flow. These approaches are particularly useful when investigating dispersal in recently altered systems, where they provide a way of inferring long‐distance dispersal between newly established populations and their interactions with existing populations. Human‐mediated biological invasions represent such altered systems which can be investigated with appropriate study designs and analyses. Here we apply temporally restricted sampling and a range of population genomic approaches to investigate dispersal in a 2004 invasion of Aedes albopictus (the Asian tiger mosquito) in the Torres Strait Islands (TSI) of Australia. We sampled mosquitoes from 13 TSI villages simultaneously and genotyped 373 mosquitoes at genome‐wide single nucleotide polymorphisms (SNPs): 331 from the TSI, 36 from Papua New Guinea (PNG) and four incursive mosquitoes detected in uninvaded regions. Within villages, spatial genetic structure varied substantially but overall displayed isolation by distance and a neighbourhood size of 232–577. Close kin dyads revealed recent movement between islands 31–203 km apart, and deep learning inferences showed incursive Ae. albopictus had travelled to uninvaded regions from both adjacent and nonadjacent islands. Private alleles and a co‐ancestry matrix indicated direct gene flow from PNG into nearby islands. Outlier analyses also detected four linked alleles introgressed from PNG, with the alleles surrounding 12 resistance‐associated cytochrome P450 genes. By treating dispersal as both an intergenerational process and a set of discrete events, we describe a highly interconnected invasive system.

High uncertainty over the future of tidal marsh birds under current sea-level rise projections - Brian T. Klingbeil; Jonathan B. Cohen; Maureen D. Correll; Christopher R. Field; Thomas P. Hodgman; Adrienne I. Kovach; Erika E. Lentz; Brian J. Olsen; W. Gregory Shriver; Whitney A. Wiest; Chris S. Elphick (Biodiversity and Conservation, 2021)

Relationships between Pacific salmon and aquatic and terrestrial ecosystems: implications for ecosystem‐based management - Jessica C. Walsh; Jane E. Pendray; Sean C. Godwin; Kyle A. Artelle; Holly K. Kindsvater; Rachel D. Field; Jennifer N. Harding; Noel R. Swain; John D. Reynolds (Ecology, 2020)
Pacific salmon influence temperate terrestrial and freshwater ecosystems through the dispersal of marine‐derived nutrients and ecosystem engineering of stream beds when spawning. They also support large fisheries, particularly along the west coast of North America. We provide a comprehensive synthesis of relationships between the densities of Pacific salmon and terrestrial and aquatic ecosystems, summarize the direction, shape, and magnitude of these relationships, and identify possible ecosystem‐based management indicators and benchmarks. We found 31 studies that provided 172 relationships between salmon density (or salmon abundance) and species abundance, species diversity, food provisioning, individual growth, concentration of marine‐derived isotopes, nutrient enhancement, phenology, and several other ecological responses. The most common published relationship was between salmon density and marine‐derived isotopes (40%), whereas very few relationships quantified ecosystem‐level responses (5%). Only 13% of all relationships tended to reach an asymptote (i.e., a saturating response) as salmon densities increased. The number of salmon killed by bears and the change in biomass of different stream invertebrate taxa between spawning and nonspawning seasons were relationships that usually reached saturation. Approximately 46% of all relationships were best described with linear or curved nonasymptotic models, indicating a lack of saturation. In contrast, 41% of data sets showed no relationship with salmon density or abundance, including many of the relationships with stream invertebrate and biofilm biomass density, marine‐derived isotope concentrations, or vegetation density. Bears required the highest densities of salmon to reach their maximum observed food consumption (i.e., 9.2 kg/m 2 to reach the 90% threshold of the relationship’s asymptote), followed by freshwater fish abundance (90% threshold = 7.3 kg/m 2 of salmon). Although the effects of salmon density on ecosystems are highly varied, it appears that several of these relationships, such as bear food consumption, could be used to develop indicators and benchmarks for ecosystem‐based fisheries management.

Morphological and genetic evidence for the separation of Phlegmariurus billardierei from P. varius (Lycopodiaceae) - Leon R. Perrie; Lara D. Shepherd; Ashley R. Field; Patrick J. Brownsey (New Zealand Journal of Botany, 2020)
Phlegmariurus varius is an Australasian species of lycophyte that has long been recognised as morphologically and ecologically variable. A recent study reported incongruence between morphological and genetic variation within New Zealand samples. However, a reappraisal and repeat of the genetic analyses of chloroplast DNA sequence data, and a more detailed examination of morphological variation, strongly supports the recognition of two species that are sympatric in New Zealand. The combination Phlegmariurus billardierei (Spring) Brownsey & Perrie is made here for plants with distinct strobili. The other species, Phlegmariurus varius (R.Br.) A.R.Field & Bostock sensu stricto , has comparatively indistinct strobili, and remains morphologically and ecologically variable even after the segregation of P. billardierei . Phlegmariurus varius is indigenous to both Australia and New Zealand, while P. billardierei is the only species of Lycopodiaceae endemic to New Zealand.

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

Fire affects the taxonomic and functional composition of soil microbial communities, with cascading effects on grassland ecosystem functioning - Sihang Yang; Qiaoshu Zheng; Yunfeng Yang; Mengting Yuan; Xingyu Ma; Nona R. Chiariello; Kathryn M. Docherty; Christopher B. Field; Jessica L. M. Gutknecht; Bruce A. Hungate; Audrey Niboyet; Xavier Le Roux; et al. (Global Change Biology, 2020)
Fire is a crucial event regulating the structure and functioning of many ecosystems. Yet few studies have focused on how fire affects taxonomic and functional diversities of soil microbial communities, along with changes in plant communities and soil carbon (C) and nitrogen (N) dynamics. Here, we analyze these effects in a grassland ecosystem 9 months after an experimental fire at the Jasper Ridge Global Change Experiment site in California, USA. Fire altered soil microbial communities considerably, with community assembly process analysis showing that environmental selection pressure was higher in burned sites. However, a small subset of highly connected taxa was able to withstand the disturbance. In addition, fire decreased the relative abundances of most functional genes associated with C degradation and N cycling, implicating a slowdown of microbial processes linked to soil C and N dynamics. In contrast, fire stimulated above‐ and belowground plant growth, likely enhancing plant–microbe competition for soil inorganic N, which was reduced by a factor of about 2. To synthesize those findings, we performed structural equation modeling, which showed that plants but not microbial communities were responsible for significantly higher soil respiration rates in burned sites. Together, our results demonstrate that fire ‘reboots’ the grassland ecosystem by differentially regulating plant and soil microbial communities, leading to significant changes in soil C and N dynamics.

The distribution and evolution of fungal symbioses in ancient lineages of land plants - William R. Rimington; Jeffrey G. Duckett; Katie J. Field; Martin I. Bidartondo; Silvia Pressel (Mycorrhiza, 2020)
An accurate understanding of the diversity and distribution of fungal symbioses in land plants is essential for mycorrhizal research. Here we update the seminal work of Wang and Qiu (Mycorrhiza 16:299-363, 2006) with a long-overdue focus on early-diverging land plant lineages, which were considerably under-represented in their survey, by examining the published literature to compile data on the status of fungal symbioses in liverworts, hornworts and lycophytes. Our survey combines data from 84 publications, including recent, post-2006, reports of Mucoromycotina associations in these lineages, to produce a list of at least 591 species with known fungal symbiosis status, 180 of which were included in Wang and Qiu (Mycorrhiza 16:299-363, 2006). Using this up-to-date compilation, we estimate that fewer than 30% of liverwort species engage in symbiosis with fungi belonging to all three mycorrhizal phyla, Mucoromycota, Basidiomycota and Ascomycota, with the last being the most widespread (17%). Fungal symbioses in hornworts (78%) and lycophytes (up to 100%) appear to be more common but involve only members of the two Mucoromycota subphyla Mucoromycotina and Glomeromycotina, with Glomeromycotina prevailing in both plant groups. Our fungal symbiosis occurrence estimates are considerably more conservative than those published previously, but they too may represent overestimates due to currently unavoidable assumptions.

Framework for quantifying population responses to disturbance reveals that coastal birds are highly resilient to hurricanes - Christopher R. Field; Katharine J. Ruskin; Jonathan B. Cohen; Thomas P. Hodgman; Adrienne I. Kovach; Brian J. Olsen; W. Gregory Shriver; Chris S. Elphick (Ecology Letters, 2019)
Changes in the frequency and severity of extreme weather may introduce new threats to species that are already under stress from gradual habitat loss and climate change. We provide a probabilistic framework that quantifies potential threats by applying concepts from ecological resilience to single populations. Our approach uses computation to compare disturbance–impacted projections to a population's normal range of variation, quantifying the full range of potential impacts. We illustrate this framework with projection models for coastal birds, which are commonly depicted as vulnerable to disturbances, especially hurricanes and oil spills. We found that populations of coastal specialists are resilient to extreme disturbances, with high resistance to the effects of short‐term reductions in vital rates and recovery within 20 years. Applying the general framework presented here across disturbance‐prone species and ecosystems would improve understanding of population resilience and generate specific projections of resilience that are needed for effective conservation planning.

Evolution and networks in ancient and widespread symbioses between Mucoromycotina and liverworts - William R. Rimington; Silvia Pressel; Jeffrey G. Duckett; Katie J. Field; Martin I. Bidartondo (Mycorrhiza, 2019)
Like the majority of land plants, liverworts regularly form intimate symbioses with arbuscular mycorrhizal fungi (Glomeromycotina). Recent phylogenetic and physiological studies report that they also form intimate symbioses with Mucoromycotina fungi and that some of these, like those involving Glomeromycotina, represent nutritional mutualisms. To compare these symbioses, we carried out a global analysis of Mucoromycotina fungi in liverworts and other plants using species delimitation, ancestral reconstruction, and network analyses. We found that Mucoromycotina are more common and diverse symbionts of liverworts than previously thought, globally distributed, ancestral, and often co-occur with Glomeromycotina within plants. However, our results also suggest that the associations formed by Mucoromycotina fungi are fundamentally different because, unlike Glomeromycotina, they may have evolved multiple times and their symbiotic networks are un-nested (i.e., not forming nested subsets of species). We infer that the global Mucoromycotina symbiosis is evolutionarily and ecologically distinctive.

Crown-of-thorns starfish impede the recovery potential of coral reefs following bleaching - M. D. E. Haywood; D. P. Thomson; R. C. Babcock; R. D. Pillans; J. K. Keesing; M. Miller; W. A. Rochester; A. Donovan; R. D. Evans; G. Shedrawi; S. N. Field (Marine Biology, 2019)

Taxonomic notes on the New Zealand flora: lectotypes in Dryopteridaceae and Nephrolepidaceae - Patrick J. Brownsey; Leon R. Perrie; Ashley R. Field (New Zealand Journal of Botany, 2019)
Dryopteridaceae is a large family of ferns with 13 indigenous species in New Zealand, and Nephrolepidaceae a small family with two indigenous species. Five lectotypes are chosen for basionyms relevant to New Zealand – Aspidium cystostegium Hook., Nephrodium decompositum var. pubescens Hook., N. pentangulare Colenso, Polypodium setosum G.Forst., and Polypodium silvaticum Colenso. A neotype is designated for Nephrodium brownii Desv. No type material has been found for Aspidium coriaceum var. acutidentatum A.Rich., and the type for this remains undesignated. Lectotypes or neotypes need to be chosen for all names at specific and infraspecific rank, for which no holotype was designated by the original author, in order to fix the application of the name concerned. Justification for the choice is provided in each case. This article is a contribution towards clarifying the taxonomic and nomenclatural status of New Zealand plants for the plant names database (Ngā Tipu Aotearoa) and the electronic Flora of New Zealand.

Taxonomic notes on the New Zealand flora: lectotypes in Isoetaceae and Lycopodiaceae - Patrick J. Brownsey; Leon R. Perrie; Ashley R. Field (New Zealand Journal of Botany, 2018)
Within the Lycopodiopsida, Lycopodiaceae is a medium‐sized family of lycophytes in New Zealand with five genera and 11 indigenous species, and Isoetaceae is a small family with one genus and two species. Fourteen lectotypes are chosen for basionyms relevant to New Zealand – Isoetes alpina Kirk, Lycopodium australianum Herter, L. billardierei Spring, L. consimile Colenso, L. curvifolium Colenso, L. distans Colenso, L. drummondii Spring , L. lessonianum A.Rich., L. novozealandicum Colenso, L. sanguisorba Spring, L. serpentinum Kunze, L. varium var. gracile Kirk, L. varium var. polaris Kirk, and Phylloglossum drummondii Kunze. No type material has been found for Lycopodium decurrens Colenso, and the type for this remains undesignated. Lectotypes need to be chosen for all names at specific and subspecific rank, for which no holotype was designated by the original author, in order to fix the application of the name concerned. Justification for the choice is provided in each case. This article is a contribution towards clarifying the taxonomic and nomenclatural status of New Zealand plants for the plant names database (Ngā Tipu Aotearoa) and the electronic Flora of New Zealand.

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Spiroplasma dominates the microbiome of khapra beetle: comparison with a congener, effects of life stage and temperature - D. M. Wilches; R. A. Laird; P. G. Fields; P. Coghlin; K. D. Floate (Symbiosis, 2018)

The microbiology and treatment of human mastitis - Angeliki Angelopoulou; Des Field; C. Anthony Ryan; Catherine Stanton; Colin Hill; R. Paul Ross (Medical Microbiology and Immunology, 2018)

Decoupled dimensions of leaf economic and anti-herbivore defense strategies in a tropical canopy tree community - K. McManus Chauvin; G. P. Asner; R. E. Martin; W. J. Kress; S. J. Wright; C. B. Field (Oecologia, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Streptococcus agalactiae Multilocus sequence type 261 is associated with mortalities in the emerging Ghanaian tilapia industry - D W Verner‐Jeffreys; T J Wallis; I Cano Cejas; D Ryder; D J Haydon; J F Domazoro; J Dontwi; T R Field; D Adjei‐Boteng; G Wood; T Bean; S W Feist (Journal of Fish Diseases, 2018)

A comparison of protein extraction methods optimizing high protein yields from marine algae and cyanobacteria - Lacey M. Field; Wayne R. Fagerberg; Kayla K. Gatto; S. Anne Böttger (Journal of Applied Phycology, 2017)

Experimental fire increases soil carbon dioxide efflux in a grassland long‐term multifactor global change experiment - Aaron L. Strong; Tera P. Johnson; Nona R. Chiariello; Christopher B. Field (Global Change Biology, 2017)
Numerous studies have demonstrated that soil respiration rates increase under experimental warming, although the long‐term, multiyear dynamics of this feedback are not well constrained. Less is known about the effects of single, punctuated events in combination with other longer‐duration anthropogenic influences on the dynamics of soil carbon (C) loss. In 2012 and 2013, we assessed the effects of decadal‐scale anthropogenic global change – warming, increased nitrogen (N) deposition, elevated carbon dioxide ( CO 2 ), and increased precipitation – on soil respiration rates in an annual‐dominated Mediterranean grassland. We also investigated how controlled fire and an artificial wet‐up event, in combination with exposure to the longer‐duration anthropogenic global change factors, influenced the dynamics of C cycling in this system. Decade‐duration surface soil warming (1–2 °C) had no effect on soil respiration rates, while +N addition and elevated CO 2 concentrations increased growing‐season soil CO 2 efflux rates by increasing annual aboveground net primary production ( NPP ) and belowground fine root production, respectively. Low‐intensity experimental fire significantly elevated soil CO 2 efflux rates in the next growing season. Based on mixed‐effects modeling and structural equation modeling, low‐intensity fire increased growing‐season soil respiration rates through a combination of three mechanisms: large increases in soil temperature (3–5 °C), significant increases in fine root production, and elevated aboveground NPP . Our study shows that in ecosystems where soil respiration has acclimated to moderate warming, further increases in soil temperature can stimulate greater soil CO 2 efflux. We also demonstrate that punctuated short‐duration events such as fire can influence soil C dynamics with implications for both the parameterization of earth system models ( ESM s) and the implementation of climate change mitigation policies that involve land‐sector C accounting.

High‐resolution tide projections reveal extinction threshold in response to sea‐level rise - Christopher R. Field; Trina S. Bayard; Carina Gjerdrum; Jason M. Hill; Susan Meiman; Chris S. Elphick (Global Change Biology, 2017)
Sea‐level rise will affect coastal species worldwide, but models that aim to predict these effects are typically based on simple measures of sea level that do not capture its inherent complexity, especially variation over timescales shorter than 1 year. Coastal species might be most affected, however, by floods that exceed a critical threshold. The frequency and duration of such floods may be more important to population dynamics than mean measures of sea level. In particular, the potential for changes in the frequency and duration of flooding events to result in nonlinear population responses or biological thresholds merits further research, but may require that models incorporate greater resolution in sea level than is typically used. We created population simulations for a threatened songbird, the saltmarsh sparrow ( Ammodramus caudacutus ), in a region where sea level is predictable with high accuracy and precision. We show that incorporating the timing of semidiurnal high tide events throughout the breeding season, including how this timing is affected by mean sea‐level rise, predicts a reproductive threshold that is likely to cause a rapid demographic shift. This shift is likely to threaten the persistence of saltmarsh sparrows beyond 2060 and could cause extinction as soon as 2035. Neither extinction date nor the population trajectory was sensitive to the emissions scenarios underlying sea‐level projections, as most of the population decline occurred before scenarios diverge. Our results suggest that the variation and complexity of climate‐driven variables could be important for understanding the potential responses of coastal species to sea‐level rise, especially for species that rely on coastal areas for reproduction.

Genome-wide meta-analyses of nonsyndromic orofacial clefts identify novel associations between FOXE1 and all orofacial clefts, and TP63 and cleft lip with or without cleft palate - Elizabeth J. Leslie; Jenna C. Carlson; John R. Shaffer; Azeez Butali; Carmen J. Buxó; Eduardo E. Castilla; Kaare Christensen; Fred W. B. Deleyiannis; L. Leigh Field; Jacqueline T. Hecht; Lina Moreno; Ieda M. Orioli; et al. (Human Genetics, 2017)

Seasonal fecundity is not related to geographic position across a species’ global range despite a central peak in abundance - Katharine J. Ruskin; Matthew A. Etterson; Thomas P. Hodgman; Alyssa C. Borowske; Jonathan B. Cohen; Chris S. Elphick; Christopher R. Field; Rebecca A. Kern; Erin King; Alison R. Kocek; Adrienne I. Kovach; Kathleen M. O’Brien; et al. (Oecologia, 2017)

Topography‐driven isolation, speciation and a global increase of endemism with elevation - Manuel J. Steinbauer; Richard Field; John‐Arvid Grytnes; Panayiotis Trigas; Claudine Ah‐Peng; Fabio Attorre; H. John B. Birks; Paulo A. V. Borges; Pedro Cardoso; Chang‐Hung Chou; Michele De Sanctis; Miguel M. de Sequeira; et al. (Global Ecology and Biogeography, 2016)
Aim Higher‐elevation areas on islands and continental mountains tend to be separated by longer distances, predicting higher endemism at higher elevations; our study is the first to test the generality of the predicted pattern. We also compare it empirically with contrasting expectations from hypotheses invoking higher speciation with area, temperature and species richness. Location Thirty‐two insular and 18 continental elevational gradients from around the world. Methods We compiled entire floras with elevation‐specific occurrence information, and calculated the proportion of native species that are endemic (‘percent endemism’) in 100‐m bands, for each of the 50 elevational gradients. Using generalized linear models, we tested the relationships between percent endemism and elevation, isolation, temperature, area and species richness. Results Percent endemism consistently increased monotonically with elevation, globally. This was independent of richness–elevation relationships, which had varying shapes but decreased with elevation at high elevations. The endemism–elevation relationships were consistent with isolation‐related predictions, but inconsistent with hypotheses related to area, richness and temperature. Main conclusions Higher per‐species speciation rates caused by increasing isolation with elevation are the most plausible and parsimonious explanation for the globally consistent pattern of higher endemism at higher elevations that we identify. We suggest that topography‐driven isolation increases speciation rates in mountainous areas, across all elevations and increasingly towards the equator. If so, it represents a mechanism that may contribute to generating latitudinal diversity gradients in a way that is consistent with both present‐day and palaeontological evidence.

Weighing the Evidence of Common Beliefs in Obesity Research - Krista Casazza; Andrew Brown; Arne Astrup; Fredrik Bertz; Charles Baum; Michelle Bohan Brown; John Dawson; Nefertiti Durant; Gareth Dutton; David A. Fields; Kevin R. Fontaine; Steven Heymsfield; et al. (Critical Reviews in Food Science and Nutrition, 2015)

Genes mirror geography in Daphnia magna - Peter D. Fields; Céline Reisser; Marinela Dukić; Christoph R. Haag; Dieter Ebert (Molecular Ecology, 2015)
Identifying the presence and magnitude of population genetic structure remains a major consideration in evolutionary biology as doing so allows one to understand the demographic history of a species as well as make predictions of how the evolutionary process will proceed. Next‐generation sequencing methods allow us to reconsider previous ideas and conclusions concerning the distribution of genetic variation, and what this distribution implies about a given species evolutionary history. A previous phylogeographic study of the crustacean Daphnia magna suggested that, despite strong genetic differentiation among populations at a local scale, the species shows only moderate genetic structure across its European range, with a spatially patchy occurrence of individual lineages. We apply RAD sequencing to a sample of D. magna collected across a wide swath of the species' Eurasian range and analyse the data using principle component analysis ( PCA ) of genetic variation and Procrustes analytical approaches, to quantify spatial genetic structure. We find remarkable consistency between the first two PCA axes and the geographic coordinates of individual sampling points, suggesting that, on a continent‐wide scale, genetic differentiation is driven to a large extent by geographic distance. The observed pattern is consistent with unimpeded (i.e. no barriers, landscape or otherwise) migration at large spatial scales, despite the fragmented and patchy nature of favourable habitats at local scales. With high‐resolution genetic data similar patterns may be uncovered for other species with wide geographic distributions, allowing an increased understanding of how genetic drift and selection have shaped their evolutionary history.

Defining and Evaluating the Umbrella Species Concept for Conserving and Restoring Landscape Connectivity - IAN BRECKHEIMER; NICK M. HADDAD; WILLIAM F. MORRIS; ANNE M. TRAINOR; WILLIAM R. FIELDS; R. TODD JOBE; BRIAN R. HUDGENS; AARON MOODY; JEFFREY R. WALTERS (Conservation Biology, 2014)
Conserving or restoring landscape connectivity between patches of breeding habitat is a common strategy to protect threatened species from habitat fragmentation. By managing connectivity for some species, usually charismatic vertebrates, it is often assumed that these species will serve as conservation umbrellas for other species. We tested this assumption by developing a quantitative method to measure overlap in dispersal habitat of 3 threatened species—a bird (the umbrella), a butterfly, and a frog—inhabiting the same fragmented landscape. Dispersal habitat was determined with Circuitscape, which was parameterized with movement data collected for each species. Despite differences in natural history and breeding habitat, we found substantial overlap in the spatial distributions of areas important for dispersal of this suite of taxa. However, the intuitive umbrella species (the bird) did not have the highest overlap with other species in terms of the areas that supported connectivity. Nevertheless, we contend that when there are no irreconcilable differences between the dispersal habitats of species that cohabitate on the landscape, managing for umbrella species can help conserve or restore connectivity simultaneously for multiple threatened species with different habitat requirements. Definición y Evaluación del Concepto de Especie Paraguas para Conservar y Restaurar la Conectividad de Paisajes

Nasal chondromesenchymal hamartomas arise secondary to germline and somatic mutations of DICER1 in the pleuropulmonary blastoma tumor predisposition disorder - Douglas R. Stewart; Yoav Messinger; Gretchen M. Williams; Jiandong Yang; Amanda Field; Kris Ann P. Schultz; Laura A. Harney; Leslie A. Doros; Louis P. Dehner; D. Ashley Hill (Human Genetics, 2014)

High pH (and not free ammonia) is responsible for Anammox inhibition in mildly alkaline solutions with excess of ammonium - D. Puyol; J. M. Carvajal-Arroyo; G. B. Li; A. Dougless; M. Fuentes-Velasco; R. Sierra-Alvarez; J. A. Field (Biotechnology Letters, 2014)

The Role of Nitrogen Deposition in Widespread Plant Community Change Across Semi-natural Habitats - Chris D. Field; Nancy B. Dise; Richard J. Payne; Andrea J. Britton; Bridget A. Emmett; Rachel C. Helliwell; Steve Hughes; Laurence Jones; Steven Lees; Jonathan R. Leake; Ian D. Leith; Gareth K. Phoenix; et al. (Ecosystems, 2014)

Aquatic invertebrate communities in tank bromeliads: how well do classic ecological patterns apply? - M. Jocque; R. Field (Hydrobiologia, 2014)

Loss of whole-tree hydraulic conductance during severe drought and multi-year forest die-off - William R. L. Anderegg; Leander D. L. Anderegg; Joseph A. Berry; Christopher B. Field (Oecologia, 2014)

Identification and Expression Profile of Two Putative Odorant-Binding Proteins from the Neotropical Brown Stink Bug, Euschistus heros (Fabricius) (Hemiptera: Pentatomidae) - L R Farias; D P Paula; J J Zhou; R Liu; G J Pappas; M C B Moraes; R A Laumann; M Borges; M A Birkett; J A Pickett; L M Field; S N Báo (Neotropical Entomology, 2014)

Importance of macroalgal fields as coral reef fish nursery habitat in north-west Australia - R. D. Evans; S. K. Wilson; S. N. Field; J. A. Y. Moore (Marine Biology, 2014)

Nitrite (not free nitrous acid) is the main inhibitor of the anammox process at common pH conditions - D. Puyol; J. M. Carvajal-Arroyo; R. Sierra-Alvarez; J. A. Field (Biotechnology Letters, 2014)

Sex differences in neuroadaptation to alcohol and withdrawal neurotoxicity - Lynda Sharrett-Field; Tracy R. Butler; Anna R. Reynolds; Jennifer N. Berry; Mark A. Prendergast (Pflügers Archiv - European Journal of Physiology, 2013)

Breeding ecology of the globally threatened Sociable Lapwing Vanellus gregarius and the demographic drivers of recent declines - Rob D. Sheldon; Johannes Kamp; Maxim A. Koshkin; Ruslan S. Urazaliev; Timur K. Iskakov; Rob H. Field; Albert R. Salemgareev; Valery V. Khrokov; Vasily A. Zhuly; Sergey L. Sklyarenko; Paul F. Donald (Journal of Ornithology, 2013)

Drought's legacy: multiyear hydraulic deterioration underlies widespread aspen forest die‐off and portends increased future risk - William R. L. Anderegg; Lenka Plavcová; Leander D. L. Anderegg; Uwe G. Hacke; Joseph A. Berry; Christopher B. Field (Global Change Biology, 2013)
Forest mortality constitutes a major uncertainty in projections of climate impacts on terrestrial ecosystems and carbon‐cycle feedbacks. Recent drought‐induced, widespread forest die‐offs highlight that climate change could accelerate forest mortality with its diverse and potentially severe consequences for the global carbon cycle, ecosystem services, and biodiversity. How trees die during drought over multiple years remains largely unknown and precludes mechanistic modeling and prediction of forest die‐off with climate change. Here, we examine the physiological basis of a recent multiyear widespread die‐off of trembling aspen ( P opulus tremuloides ) across much of western N orth A merica. Using observations from both native trees while they are dying and a rainfall exclusion experiment on mature trees, we measure hydraulic performance over multiple seasons and years and assess pathways of accumulated hydraulic damage. We test whether accumulated hydraulic damage can predict the probability of tree survival over 2 years. We find that hydraulic damage persisted and increased in dying trees over multiple years and exhibited few signs of repair. This accumulated hydraulic deterioration is largely mediated by increased vulnerability to cavitation, a process known as cavitation fatigue. Furthermore, this hydraulic damage predicts the probability of interyear stem mortality. Contrary to the expectation that surviving trees have weathered severe drought, the hydraulic deterioration demonstrated here reveals that surviving regions of these forests are actually more vulnerable to future droughts due to accumulated xylem damage. As the most widespread tree species in N orth A merica, increasing vulnerability to drought in these forests has important ramifications for ecosystem stability, biodiversity, and ecosystem carbon balance. Our results provide a foundation for incorporating accumulated drought impacts into climate–vegetation models. Finally, our findings highlight the critical role of drought stress accumulation and repair of stress‐induced damage for avoiding plant mortality, presenting a dynamic and contingent framework for drought impacts on forest ecosystems.

A Strategy for Prioritizing Threats and Recovery Actions for At-Risk Species - Catherine R. Darst; Philip J. Murphy; Nathan W. Strout; Steven P. Campbell; Kimberleigh J. Field; Linda Allison; Roy C. Averill-Murray (Environmental Management, 2013)

Mevalocidin: A Novel, Phloem Mobile Phytotoxin from Fusarium DA056446 and Rosellinia DA092917 - B. Clifford Gerwick; William K. Brewster; Gerrit J. deBoer; Steve C. Fields; Paul R. Graupner; Donald R. Hahn; Cedric J. Pearce; Paul R. Schmitzer; Jeffery D. Webster (Journal of Chemical Ecology, 2013)

Bayesian inference of a complex invasion history revealed by nuclear and chloroplast genetic diversity in the colonizing plant, S ilene latifolia - Stephen R. Keller; Kimberly J. Gilbert; Peter D. Fields; Douglas R. Taylor (Molecular Ecology, 2012)
Species invading new ranges are subject to a series of demographic events that can strongly shape genetic diversity. Describing this demographic history is important for understanding where invasive species come from and how they spread, and is critical to testing hypotheses of postinvasion adaptation. Here, we analyse nuclear and chloroplast genetic diversity to study the invasion history of the widespread colonizing weed, S ilene latifolia ( C aryophyllaceae). Bayesian clustering and PCA revealed strong population structure in the native range of Europe, and although genotypes from multiple native sources were present in the introduced range of North America, the spatial distribution of genetic variance was dramatically reorganized. Using approximate B ayesian computation ( ABC ), we compared support for different invasion scenarios, including the number and size of independent introduction events and the amount of admixture occurring between sources of introduced genotypes. Our results supported independent introductions into eastern and western North America, with the latter forming a bridgehead for a secondary invasion into the G reat L akes region of central N orth A merica. Despite small estimated founder population sizes, the duration of the demographic bottleneck after the initial introduction appeared extremely short‐lived. This pattern of repeated colonization and rapid expansion has effectively eroded the strong population structure and cytonuclear associations present in Europe, but has retained overall high genetic diversity since invasion. Our results highlight the flexibility of the ABC approach for constructing a narrative of the demographic history of species invasions and provide baseline for future studies of evolutionary changes in introduced S. latifolia populations.

Eruption of kimberlite magmas: physical volcanology, geomorphology and age of the youngest kimberlitic volcanoes known on earth (the Upper Pleistocene/Holocene Igwisi Hills volcanoes, Tanzania) - Richard J. Brown; S. Manya; I. Buisman; G. Fontana; M. Field; C. Mac Niocaill; R. S. J. Sparks; F. M. Stuart (Bulletin of Volcanology, 2012)

Magma storage conditions beneath Dabbahu Volcano (Ethiopia) constrained by petrology, seismicity and satellite geodesy - L. Field; J. Blundy; R. A. Brooker; T. Wright; G. Yirgu (Bulletin of Volcanology, 2012)

Refining instrument attachment on phocid seals - Iain C. Field; Robert G. Harcourt; Lars Boehme; P. J. Nico de Bruyn; Jean‐Benoit Charrassin; Clive R. McMahon; Marthán N. Bester; Mike A. Fedak; Mark A. Hindell (Marine Mammal Science, 2012)

Comparison of the Potency of the Lipid II Targeting Antimicrobials Nisin, Lacticin 3147 and Vancomycin Against Gram-Positive Bacteria - Catalin Iancu; Aoife Grainger; Des Field; Paul D. Cotter; Colin Hill; R. Paul Ross (Probiotics and Antimicrobial Proteins, 2012)

Trophic ecology of reef sharks determined using stable isotopes and telemetry - C. W. Speed; M. G. Meekan; I. C. Field; C. R. McMahon; K. Abrantes; C. J. A. Bradshaw (Coral Reefs, 2012)

Evidence for reproductive philopatry in the bull shark Carcharhinus leucas - B. J. Tillett; M. G. Meekan; I. C. Field; D. C. Thorburn; J. R. Ovenden (Journal of Fish Biology, 2012)
Reproductive philopatry in bull sharks Carcharhinus leucas was investigated by comparing mitochondrial (NADH dehydrogenase subunit 4, 797 base pairs and control region genes 837 base pairs) and nuclear (three microsatellite loci) DNA of juveniles sampled from 13 river systems across northern Australia. High mitochondrial and low microsatellite genetic diversity among juveniles sampled from different rivers (mitochondrial φ ST = 0·0767, P F ST = −0·0022, P > 0·05) supported female reproductive philopatry. Genetic structure was not further influenced by geographic distance ( P > 0·05) or long‐shore barriers to movement ( P > 0·05). Additionally, results suggest that C. leucas in northern Australia has a long‐term effective population size of 11 000–13 000 females and has undergone population bottlenecks and expansions that coincide with the timing of the last ice‐ages.

Neutral metallated and meso-substituted porphyrins as antimicrobial agents against Gram-positive pathogens - W. N. Burda; K. B. Fields; J. B. Gill; R. Burt; M. Shepherd; X. P. Zhang; L. N. Shaw (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Pleistocene isolation, secondary introgression and restricted contemporary gene flow in the pig-eye shark, Carcharhinus amboinensis across northern Australia - B. J. Tillett; M. G. Meekan; D. Broderick; I. C. Field; G. Cliff; J. R. Ovenden (Conservation Genetics, 2012)

Evaluation and remediation of bulk soap dispensers for biofilm - Lindsey A. Lorenz; Bradley D. Ramsay; Darla M. Goeres; Matthew W. Fields; Carrie A. Zapka; David R. Macinga (Biofouling, 2012)

The IPCC AR5 guidance note on consistent treatment of uncertainties: a common approach across the working groups - Michael D. Mastrandrea; Katharine J. Mach; Gian-Kasper Plattner; Ottmar Edenhofer; Thomas F. Stocker; Christopher B. Field; Kristie L. Ebi; Patrick R. Matschoss (Climatic Change, 2011)

The volatile content of hypabyssal kimberlite magmas: some constraints from experiments on natural rock compositions - Richard A. Brooker; R. Stephen J. Sparks; Janine L. Kavanagh; Matthew Field (Bulletin of Volcanology, 2011)

Emplacement temperatures of pyroclastic and volcaniclastic deposits in kimberlite pipes in southern Africa - Giovanni Fontana; Conall Mac Niocaill; Richard J. Brown; R. Stephen J. Sparks; Matthew Field (Bulletin of Volcanology, 2011)

Geology of the BK9 kimberlite (Damtshaa, Botswana): implications for the formation of dark volcaniclastic kimberlite - B. Buse; R. S. J. Sparks; M. Field; J. C. Schumacher; K. Chisi; T. Tlhaodi (Bulletin of Volcanology, 2011)

Active and effective nest defence by males in a social apoid wasp - Eric R. Lucas; Jeremy Field (Behavioral Ecology and Sociobiology, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 3. An Evaluation of the Risks to Benthic Invertebrates Associated With Exposure to Contaminated Sediments - Donald D. MacDonald; Christopher G. Ingersoll; Nile E. Kemble; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Gary Gaston; Denise Sanger; R. Scott Carr; James Biedenbach; Ron Gouguet; John Kern; et al. (Archives of Environmental Contamination and Toxicology, 2011)

AgrAbility Mental/Behavioral Health For Farm/Ranch Families With Disabilities - Roberta A. Schweitzer; Gail R. Deboy; Paul J. Jones; William E. Field (Journal of Agromedicine, 2011)

Social and genetic structure in colonies of the social wasp Microstigmus nigrophthalmus - E. R. Lucas; R. P. Martins; L. R. S. Zanette; J. Field (Insectes Sociaux, 2011)

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Growth of bultfonteinite and hydrogarnet in metasomatized basalt xenoliths in the B/K9 kimberlite, Damtshaa, Botswana: insights into hydrothermal metamorphism in kimberlite pipes - Ben Buse; John C. Schumacher; R. Stephen J. Sparks; Matthew Field (Contributions to Mineralogy and Petrology, 2010)

How effective are non-destructive sampling methods to assess aquatic invertebrate diversity in bromeliads? - M. Jocque; A. Kernahan; A. Nobes; C. Willians; R. Field (Hydrobiologia, 2010)

Effects of alcohol preload on attentional bias towards cocaine-related cues - Catharine Montgomery; Matt Field; Amanda M. Atkinson; Jon C. Cole; Andrew J. Goudie; Harry R. Sumnall (Psychopharmacology, 2010)

Calmodulin-binding transcription activator 1 mediates auxin signaling and responds to stresses in Arabidopsis - Yael Galon; Roni Aloni; Dikla Nachmias; Orli Snir; Ester Feldmesser; Sarah Scrase-Field; Joy M. Boyce; Nicolas Bouché; Marc R. Knight; Hillel Fromm (Planta, 2010)

Fed-batch operation of an industrial cell culture process in shaken microwells - N. J. Silk; S. Denby; G. Lewis; M. Kuiper; D. Hatton; R. Field; F. Baganz; Gary J. Lye (Biotechnology Letters, 2010)

Occurrence and characterization of Salmonella enterica subspecies enterica serovar 9,12:l,v:- strains from Bulgaria, Denmark, and the United States - P. Petrov; R. S. Hendriksen; T. Kantardjiev; G. Asseva; G. Sørensen; P. Fields; M. Mikoleit; J. Whichard; J. R. McQuiston; M. Torpdahl; F. M. Aarestrup; F. J. Angulo (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Distribution of Anthocyanins Delivered from a Bioadhesive Black Raspberry Gel Following Topical Intraoral Application in Normal Healthy Volunteers - Carlos M. Ugalde; Zhongfa Liu; Chen Ren; Kenneth K. Chan; Kapila A. Rodrigo; Yhonghua Ling; Peter E. Larsen; Guillermo E. Chacon; Gary D. Stoner; Russell J. Mumper; Henry W. Fields; Susan R. Mallery (Pharmaceutical Research, 2009)

Geology of a complex kimberlite pipe (K2 pipe, Venetia Mine, South Africa): insights into conduit processes during explosive ultrabasic eruptions - R. J. Brown; M. Tait; M. Field; R. S. J. Sparks (Bulletin of Volcanology, 2009)

Spatial species‐richness gradients across scales: a meta‐analysis - Richard Field; Bradford A. Hawkins; Howard V. Cornell; David J. Currie; J. Alexandre F. Diniz‐Filho; Jean‐François Guégan; Dawn M. Kaufman; Jeremy T. Kerr; Gary G. Mittelbach; Thierry Oberdorff; Eileen M. O’Brien; John R. G. Turner (Journal of Biogeography, 2009)
Aim We surveyed the empirical literature to determine how well six diversity hypotheses account for spatial patterns in species richness across varying scales of grain and extent. Location Worldwide. Methods We identified 393 analyses (‘cases’) in 297 publications meeting our criteria. These criteria included the requirement that more than one diversity hypothesis was tested for its relationship with species richness. We grouped variables representing the hypotheses into the following ‘correlate types’: climate/productivity, environmental heterogeneity, edaphics/nutrients, area, biotic interactions and dispersal/history (colonization limitation or other historical or evolutionary effect). For each case we determined the ‘primary’ variable: the one most strongly correlated with taxon richness. We defined ‘primacy’ as the proportion of cases in which each correlate type was represented by the primary variable, relative to the number of times it was studied. We tested for differences in both primacy and mean coefficient of determination of the primary variable between the hypotheses and between categories of five grouping variables: grain, extent, taxon (animal vs. plant), habitat medium (land vs. water) and insularity (insular vs. connected). Results Climate/productivity had the highest overall primacy, and environmental heterogeneity and dispersal/history had the lowest. Primacy of climate/productivity was much higher in large‐grain and large‐extent studies than at smaller scales. It was also higher on land than in water, and much higher in connected systems than in insular ones. For other hypotheses, differences were less pronounced. Throughout, studies on plants and animals showed similar patterns. Coefficients of determination of the primary variables differed little between hypotheses and across the grouping variables, the strongest effects being low means in the smallest grain class and for edaphics/nutrients variables, and a higher mean for water than for land in connected systems but vice versa in insular systems. We highlight areas of data deficiency. Main conclusions Our results support the notion that climate and productivity play an important role in determining species richness at large scales, particularly for non‐insular, terrestrial habitats. At smaller extents and grain sizes, the primacy of the different types of correlates appears to differ little from null expectation. In our analysis, dispersal/history is rarely the best correlate of species richness, but this may reflect the difficulty of incorporating historical factors into regression models, and the collinearity between past and current climates. Our findings are consistent with the view that climate determines the capacity for species richness. However, its influence is less evident at smaller spatial scales, probably because (1) studies small in extent tend to sample little climatic range, and (2) at large grains some other influences on richness tend to vary mainly within the sampling unit.

Guarding against oversimplifying the fundamental drivers of southern elephant seal population dynamics - C. R. McMahon; I. C. Field; M. A. Hindell; S. C. De Little; C. J. A. Bradshaw (Journal of Biogeography, 2008)

Genetic relatedness in early associations of Polistes dominulus : from related to unrelated helpers - LORENZO R. S. ZANETTE; JEREMY FIELD (Molecular Ecology, 2008)
Indirect benefits obtained through the reproduction of relatives are fundamental in the formation and maintenance of groups. Here, we examine the hypothesis that females of the temperate paper wasp Polistes dominulus preferentially form groups with close relatives. Genetic relatedness data were obtained for 180 groups of females collected at the early stages of the nesting cycle of a large population of P. dominulus in two sites in southwestern Spain. Average within‐group relatedness values ranged from 0.189 to 0.491. Foundresses on early nests were significantly more closely related than females in winter aggregations or in stable groups (just before workers emerged). Within‐group relatedness values were independent of group size. The vast majority of worker‐producing nests ( c . 85%) had one or more females that were unrelated (or distantly related) to the remaining members of the group. These results provide further support to the hypothesis that indirect fitness benefits alone are unlikely to explain why P. dominulus foundresses form cooperative associations.

Surface plasmon resonance imaging for real-time, label-free analysis of protein interactions with carbohydrate microarrays - Rositsa Karamanska; Jonathan Clarke; Ola Blixt; James I. MacRae; Jiquan Q. Zhang; Paul R. Crocker; Nicolas Laurent; Adam Wright; Sabine L. Flitsch; David A. Russell; Robert A. Field (Glycoconjugate Journal, 2008)

Formulation and In-Vitro and In-Vivo Evaluation of a Mucoadhesive Gel Containing Freeze Dried Black Raspberries: Implications for Oral Cancer Chemoprevention - Susan R. Mallery; Gary D. Stoner; Peter E. Larsen; Henry W. Fields; Kapila A. Rodrigo; Steven J. Schwartz; Qingguo Tian; Jin Dai; Russell J. Mumper (Pharmaceutical Research, 2007)

Age-related shifts in the diet composition of southern elephant seals expand overall foraging niche - Iain C. Field; Corey J. A. Bradshaw; John van den Hoff; Harry R. Burton; Mark A. Hindell (Marine Biology, 2007)

Agri-environment schemes and butterflies: the utilisation of two metre arable field margins - R. G. Field; T. Gardiner; C. F. Mason; J. Hill (Biodiversity and Conservation, 2007)

Interactive Effects of Fire, Elevated Carbon Dioxide, Nitrogen Deposition, and precipitation on a California Annual Grassland - Hugh A. L. Henry; Nona R. Chiariello; Peter M. Vitousek; Harold A. Mooney; Christopher B. Field (Ecosystems, 2006)

Comparative field performance over 3 years and two sites of transgenic wheat lines expressing HMW subunit transgenes - Peter R. Shewry; Stephen Powers; J. Michael Field; Roger J. Fido; Huw D. Jones; Gillian M. Arnold; Jevon West; Paul A. Lazzeri; Pilar Barcelo; Francisco Barro; Arthur S. Tatham; Frank Bekes; et al. (Theoretical and Applied Genetics, 2006)

Frequent Tanning Bed Use, Weight Concerns, and Other Health Risk Behaviors in Adolescent Females (United States) - David L. O’Riordan; Alison E. Field; Alan C. Geller; Daniel R. Brooks; Gideon Aweh; Graham A. Colditz; A. Lindsay Frazier (Cancer Causes & Control, 2006)

Internal transcribed spacer sequence analyses indicate cytoevolutionary patterns within Brachycome Cass. (Asteraceae) - B. L. Field; A. Houben; J. N. Timmis; C. R. Leach (Plant Systematics and Evolution, 2006)

Pleistocene fluvial sediments, palaeontology and archaeology of the upper River Thames at Latton, Wiltshire, England - S. G. Lewis; D. Maddy; C. Buckingham; G. R. Coope; M. H. Field; D. H. Keen; A. W. G. Pike; D. A. Roe; R. G. Scaife; K. Scott (Journal of Quaternary Science, 2006)
Pleistocene fluvial sediments of the Northmoor Member of the Upper Thames Formation exposed at Latton, Wiltshire, record episodic deposition close to the Churn–Thames confluence possibly spanning the interval from Marine Isotope Stages (MIS) 7 to 2. The sequence is dominated by gravel facies, indicating deposition by a high‐energy, gravel‐bed river. A number of fine‐grained organic sediment bodies within the sequence have yielded palaeoenvironmental and biostratigraphical data from Mollusca, Coleoptera, vertebrates, pollen and plant macrofossils. The basal deposit (Facies Association A) contains faunal material indicating temperate conditions. Most of the palaeontological evidence including a distinctive small form of mammoth ( Mammuthus cf. trogontherii ), together with the U‐series age estimate of >147.4 ± 20 kyr suggest correlation with MIS 7. The overlying deposits (Facies Associations B and C) represent deposition under a range of climatic conditions. Two fine‐grained organic deposits occurred within Association B; one (Association Ba) in the northern part of the pit as a channel fill and the other (Association Bb) in its southern part as a scour‐fill deposit. The coleopteran assemblages from Ba, indicate that it accumulated under temperate oceanic conditions, while Bb, which also yielded a radiocarbon age estimate of 39 560 ± 780 14 C yr BP, was formed under much colder and more continental climatic conditions. The sequence is considered to represent deposition within an alluvial fan formed at the Churn–Thames confluence; a depositional scenario which may account for the juxtaposition of sediments and fossils of widely differing age within the same altitudinal range. Copyright © 2006 John Wiley & Sons, Ltd.

Countryside Stewardship Scheme and Butterflies: A Study of Plant and Butterfly Species Richness - R. G. Field; T. Gardiner; C. F. Mason; J. Hill (Biodiversity and Conservation, 2006)

Zero tolerance ecology: improving ecological inference by modelling the source of zero observations - Tara G. Martin; Brendan A. Wintle; Jonathan R. Rhodes; Petra M. Kuhnert; Scott A. Field; Samantha J. Low‐Choy; Andrew J. Tyre; Hugh P. Possingham (Ecology Letters, 2005)
A common feature of ecological data sets is their tendency to contain many zero values. Statistical inference based on such data are likely to be inefficient or wrong unless careful thought is given to how these zeros arose and how best to model them. In this paper, we propose a framework for understanding how zero‐inflated data sets originate and deciding how best to model them. We define and classify the different kinds of zeros that occur in ecological data and describe how they arise: either from ‘true zero’ or ‘false zero’ observations. After reviewing recent developments in modelling zero‐inflated data sets, we use practical examples to demonstrate how failing to account for the source of zero inflation can reduce our ability to detect relationships in ecological data and at worst lead to incorrect inference. The adoption of methods that explicitly model the sources of zero observations will sharpen insights and improve the robustness of ecological analyses.

Effect of oxygen limitation on the in vitro antimicrobial susceptibility of clinical isolates of Pseudomonas aeruginosa grown planktonically and as biofilms - T. R. Field; A. White; J. S. Elborn; M. M. Tunney (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Resource partitioning through oceanic segregation of foraging juvenile southern elephant seals (Mirounga leonina) - Iain C. Field; Corey J. A. Bradshaw; Harry R. Burton; Michael D. Sumner; Mark A. Hindell (Oecologia, 2005)

Predictions and tests of climate‐based hypotheses of broad‐scale variation in taxonomic richness - David J. Currie; Gary G. Mittelbach; Howard V. Cornell; Richard Field; Jean‐Francois Guégan; Bradford A. Hawkins; Dawn M. Kaufman; Jeremy T. Kerr; Thierry Oberdorff; Eileen O'Brien; J. R. G. Turner (Ecology Letters, 2004)
Broad‐scale variation in taxonomic richness is strongly correlated with climate. Many mechanisms have been hypothesized to explain these patterns; however, testable predictions that would distinguish among them have rarely been derived. Here, we examine several prominent hypotheses for climate–richness relationships, deriving and testing predictions based on their hypothesized mechanisms. The ‘energy–richness hypothesis’ (also called the ‘more individuals hypothesis’) postulates that more productive areas have more individuals and therefore more species. More productive areas do often have more species, but extant data are not consistent with the expected causal relationship from energy to numbers of individuals to numbers of species. We reject the energy–richness hypothesis in its standard form and consider some proposed modifications. The ‘physiological tolerance hypothesis’ postulates that richness varies according to the tolerances of individual species for different sets of climatic conditions. This hypothesis predicts that more combinations of physiological parameters can survive under warm and wet than cold or dry conditions. Data are qualitatively consistent with this prediction, but are inconsistent with the prediction that species should fill climatically suitable areas. Finally, the ‘speciation rate hypothesis’ postulates that speciation rates should vary with climate, due either to faster evolutionary rates or stronger biotic interactions increasing the opportunity for evolutionary diversification in some regions. The biotic interactions mechanism also has the potential to amplify shallower, underlying gradients in richness. Tests of speciation rate hypotheses are few (to date), and their results are mixed.

Biodegradability of chlorinated solvents and related chlorinated aliphatic compounds - J.A Field; R Sierra-Alvarez (Reviews in Environmental Science and Bio/Technology, 2004)

Minimizing the cost of environmental management decisions by optimizing statistical thresholds - Scott A. Field; Andrew J. Tyre; Niclas Jonzén; Jonathan R. Rhodes; Hugh P. Possingham (Ecology Letters, 2004)
Environmental management decisions are prone to expensive mistakes if they are triggered by hypothesis tests using the conventional Type I error rate ( α ) of 0.05. We derive optimal α ‐levels for decision‐making by minimizing a cost function that specifies the overall cost of monitoring and management. When managing an economically valuable koala population, it shows that a decision based on α = 0.05 carries an expected cost over $5 million greater than the optimal decision. For a species of such value, there is never any benefit in guarding against the spurious detection of declines and therefore management should proceed directly to recovery action. This result holds in most circumstances where the species’ value substantially exceeds its recovery costs. For species of lower economic value, we show that the conventional α ‐level of 0.05 rarely approximates the optimal decision‐making threshold. This analysis supports calls for reversing the statistical ‘burden of proof’ in environmental decision‐making when the cost of Type II errors is relatively high.

Seasonal use of oceanographic and fisheries management zones by juvenile southern elephant seals ( Mirounga leonina ) from Macquarie Island - Iain C. Field; Corey J. A. Bradshaw; Harry R. Burton; Mark A. Hindell (Polar Biology, 2004)

Accuracy, efficiency and robustness of four algorithms allowing full sibship reconstruction from DNA marker data - K. Butler; C. Field; C. M. Herbinger; B. R. Smith (Molecular Ecology, 2004)
In the problem of reconstructing full sib pedigrees from DNA marker data, three existing algorithms and one new algorithm are compared in terms of accuracy, efficiency and robustness using real and simulated data sets. An algorithm based on the exclusion principle and another based on a maximization of the Simpson index were very accurate at reconstructing data sets comprising a few large families but had problems with data sets with limited family structure, while a Markov Chain Monte Carlo (MCMC) algorithm based on the maximization of a partition score had the opposite behaviour. An MCMC algorithm based on maximizing the full joint likelihood performed best in small data sets comprising several medium‐sized families but did not work well under most other conditions. It appears that the likelihood surface may be rough and presents challenges for the MCMC algorithm to find the global maximum. This likelihood algorithm also exhibited problems in reconstructing large family groups, due possibly to limits in computational precision. The accuracy of each algorithm improved with an increasing amount of information in the data set, and was very high with eight loci with eight alleles each. All four algorithms were quite robust to deviation from an idealized uniform allelic distribution, to departures from idealized Mendelian inheritance in simulated data sets and to the presence of null alleles. In contrast, none of the algorithms were very robust to the probable presence of error/mutation in the data. Depending upon the type of mutation or errors and the algorithm used, between 70 and 98% of the affected individuals were classified improperly on average.

Evaluation of Numerical Sediment Quality Targets for the St. Louis River Area of Concern - J. L. Crane; D. D. MacDonald; C. G. Ingersoll; D. E. Smorong; R. A. Lindskoog; C. G. Severn; T. A. Berger; L. J. Field (Archives of Environmental Contamination and Toxicology, 2002)

Resource Optimization and Symbiotic Nitrogen Fixation - E. B. Rastetter; P. M. Vitousek; C. Field; G. R. Shaver; D. Herbert; G. I. gren (Ecosystems, 2001)

Human Demographic Trends and Landscape Level Forest Management in the Northwest Wisconsin Pine Barrens - Volker C. Radeloff; Roger B. Hammer; Paul R. Voss; Alice E. Hagen; Donald R. Field; David J. Mladenoff (Forest Science, 2001)
The effects of landscape pattern on forest ecosystems have been a recent focus in forest science. Forest managers are increasingly considering landscape level processes in their management. Natural disturbance patterns provide one baseline for such management. What has been largely ignored is the pattern of human habitation patterns (i.e., housing), on landscapes. The objective of this study is to discuss landscape level management options for the northwest Wisconsin Pine Barrens based on both landscape ecology and the human demographics of the region. Using the 1990 U. S. Decennial Census we examined current housing density, seasonal housing unit concentration, historic housing density change and projected future housing densities. These data were related to land cover and land ownership data using a GIS. Housing density increase was particularly pronounced in the central Pine Barrens, an area where seasonal housing units are common. Lakes and streams were more abundant in areas that exhibited highest growth. Within national forest lands, 80% of the area contained no housing units. In contrast, only 12% of the area in small private land ownership contained no housing. These results are integrated with previous studies of presettlement vegetation and landscape change to discuss landscape level management suggestions for the Pine Barrens. For. Sci. 47(2):229–241.

Mass of weaned elephant seal pups in areas of low and high human presence - Georg H. Engelhard; John van den Hoff; Martijn Broekman; Antonie N.J. Baarspul; Iain Field; Harry R. Burton; Peter J.H. Reijnders (Polar Biology, 2001)

Species‐specific responses of plant communities to altered carbon and nutrient availability - Geeske Joel; F. Stuart Chapin; Nona R. Chiariello; Susan S. Thayer; Christopher B. Field (Global Change Biology, 2001)
Summary In a field microcosm experiment, species‐specific responses of aboveground biomass of two California annual grassland communities to elevated CO 2 and nutrient availability were investigated. One community grows on shallow, nutrient‐poor serpentine‐derived soil whereas the other occurs on deeper, modestly fertile sandstone/greenstone‐derived substrate. In most species, CO 2 effects did not appear until late in the growing season, probably because the elevated CO 2 increased water‐use‐efficiency easing, the onset of the summer drought. Responses of aboveground biomass to elevated CO 2 differed depending on nutrient availability. Similarly, biomass responses to nutrient treatments differed depending on the CO 2 status. For the majority of the species, production increased most under elevated CO 2 with added nutrients (N,P,K, and micro nutrients). Some species were losers under conditions that increased overall community production, including Bromus hordeaceus in the serpentine community (negative biomass response under elevated CO 2 ) and Lotus wrangelianus in both communities (negative biomass response with added nitrogen). Treatment and competitive effects on species‐specific biomass varied in both magnitude and direction, especially in the serpentine community, significantly affecting community structure. Individual resource environments are likely to be affected by neighbouring plants, and these competitive interactions complicate predictions of species' responses to elevated CO 2 .

Introduction - Joseph A. Berry; Christopher B. Field; Arthur R. Grossman (Photosynthesis Research, 2001)

Middle Pleistocene interglacial deposits at Barling, Essex, England: evidence for a longer chronology for the Thames terrace sequence - D. R. Bridgland; R. C. Preece; H. M. Roe; R. M. Tipping; G. R. Coope; M. H. Field; J. E. Robinson; D. C. Schreve; K. Crowe (Journal of Quaternary Science, 2001)
Results are presented from a multidisciplinary study of fossiliferous interglacial deposits on the northern side of the Thames estuary. These fill a channel cut into London Clay bedrock and overlain by the Barling Gravel, a Thames–Medway deposit equivalent to the Lynch Hill and Corbets Tey Gravels of the Middle and Lower Thames, respectively. The channel sediments yielded diverse molluscan and ostracod assemblages, both implying fully interglacial conditions and a slight brackish influence. Pollen analysis has shown that the deposits accumulated during the early part of an interglacial. Plant macrofossils, particularly the abundance of Trapa natans , reinforce the interglacial character of the palaeontological evidence. A beetle fauna, which includes four taxa unknown in Britain at present, has allowed quantification of palaeotemperature using the mutual climatic range method ( T max 17 to 26 °C; T min −11 to 13 °C). A few vertebrate remains have been recovered from the interglacial deposits, but a much larger fauna, as well as Palaeolithic artefacts, is known from the overlying Barling Gravel. The age of the interglacial deposits is inferential. The geological context suggests a late Middle Pleistocene interglacial, part of the post‐diversion Thames system and therefore clearly post‐Anglian. This conclusion is supported by amino acid ratios from the shells of freshwater molluscs. The correlation of the overlying Barling Gravel with the Lynch Hill/Corbets Tey aggradation of the Thames valley constrains the age of the Barling interglacial to marine oxygen isotope stages 11 or 9. The presence of Corbicula fluminalis and Pisidium clessini confirms a pre‐Ipswichian (marine oxygen isotope substage 5e) age and their occurrence in the early part of the interglacial cycle at Barling precludes correlation with marine oxygen isotope stage 11, as these taxa occur only later in that interglacial at sites such as Swanscombe and Clacton. Thus by process of elimination a marine oxygen isotope stage 9 age would appear probable. Copyright © 2001 John Wiley & Sons, Ltd.

Commentary: Carbon Metabolism of the Terrestrial Biosphere: A Multitechnique Approach for Improved Understanding - J. G. Canadell; H. A. Mooney; D. D. Baldocchi; J. A. Berry; J. R. Ehleringer; C. B. Field; S. T. Gower; D. Y. Hollinger; J. E. Hunt; R. B. Jackson; S. W. Running; G. R. Shaver; et al. (Ecosystems, 2000)

Sedimentology, palaeoecology and geochronology of Last Interglacial deposits from Deeping St James, Lincolnshire, England - D. H. Keen; M. D. Bateman; G. R. Coope; M. H. Field; H. E. Langford; J. S. Merry; T. M. Mighall (Journal of Quaternary Science, 1999)

Diet quality does not affect resting metabolic rate or body temperatures selected by an herbivorous lizard - K. E. Nussear; R. E. Espinoza; C. M. Gubbins; K. J. Field; J. P. Hayes (Journal of Comparative Physiology B, 1998)

Plant species-specific changes in root-inhabiting fungi in a California annual grassland: responses to elevated CO 2 and nutrients - Matthias C. Rillig; Michael F. Allen; John N. Klironomos; Nona R. Chiariello; Christopher B. Field (Oecologia, 1998)

Middle Pleistocene deposits at Frog Hall Pit, Stretton‐on-Dunsmore, Warwickshire, English Midlands, and their implications for the age of the type Wolstonian - D. H. Keen; G. R. Coope; R. L. Jones; M. H. Field; H. I. Griffiths; S. G. Lewis; D. Q. Bowen (Journal of Quaternary Science, 1997)

Middle Pleistocene deposits at Frog Hall Pit, Stretton-on-Dunsmore, Warwickshire, English Midlands, and their implications for the age of the type Wolstonian - D. H. Keen; G. R. Coope; R. L. Jones; M. H. Field; H. I. Griffiths; S. G. Lewis; D. Q. Bowen (Journal of Quaternary Science, 1997)

Isolation and characterization of novel waterfowl microsatellite loci: cross‐species comparisons and research applications - R. L. Fields; K. T. Scribner (Molecular Ecology, 1997)

Alternative products from trees and shrubs to ?The role of trees in sustainable agriculture? conference, Albury, September 30th?October 3rd 1991 - A. Boutland; M. Robinson; J. Field; M. Scheltema; B. Hawkins; P. Bulman; J. Scarvelis; B. Mason; M. Wallace; M. Castley; P. A. Ryan; R. T. Henderson; et al. (Agroforestry Systems, 1992)

Reinfection and reactivation of equine herpesvirus-1 in the mouse - H. J. Field; A. R. Awan; R. de la Fuente (Archives of Virology, 1992)

Pathogenesis of equine herpesvirus-1 in specific pathogen-free foals: primary and secondary infections and reactivation - J. S. Gibson; J. D. Slater; A. R. Awan; H. J. Field (Archives of Virology, 1992)